Formation of sociolinguistic competence in students of junior courses of economic specialties - Петренко, Оксана Дмитрівна (Eduweb, la revista de Tecnología de Información y Comunicación en Educación, 2023)
The use of sociolinguistic competence as a tool for developing foreign language learning abilities is often used by modern educational institutions. The article aims to analyze the formation of students' sociolinguistic competence, their ability to maintain a varied discourse, and their use of special styles of speech in different social environments and communication situations. An important area for research is the analysis of modern interactive and digital technologies used in educational institutions to improve the professional abilities of students. The article focuses on the theoretical aspects of sociolinguistic competence, sources of its origin, principles of formation, and aspects of its implementation in professional activity. The key principles of its development are outlined and the means that can be used to improve it are presented. The author suggests appropriate means for the formation of sociolinguistic competence in the context of the spread of actualization of the use of a foreign language both in the professional environment and in everyday life, which is due to globalization. The obtained results of the study can be used in the practice of educational institutions to improve the quality of sociolinguistic competence formation.
Formación de la competencia sociolingüística en estudiantes de cursos inferiores de especialidades económicas
Keywords: sociolinguistic competence, speech style, professional discourse, educational institutions, lexical and semantic groups, professional competence